Analysis of Taboo Language Used in The Wolf of Wall Street Movie - Nurcholish M; Muhammad Taufik; Andi Syurganda (ASHLITION : Ash-Shahabah English Literature, Linguistics, & Education, 2023)
This study examined taboo language in the film "The Wolf of Wall Street" to achieve two goals: 1) identifying its types, and 2) describing its functions. Employing a descriptive qualitative approach, the researcher utilized Batistella (2005: 72) and Wardhaugh (2006: 239) theories to analyze the language types and functions. Findings showed four taboo language types: Efficacy, Obscenity, Vulgarity, and Obscenity. Four functions were identified: Drawing Attention, Showing Contempt, Being Provocative, and Mocking Authority. The predominant type was profanity, appearing 82 times (51.25%), followed by obscenities (30 times, 18.75%), epithets (28 times, 17.5%), and vulgar language (20 times, 12.5%). The most frequent function was drawing attention, occurring 63 times (48.84%), followed by provocation (35 times, 27.13%), contempt (26 times, 20.15%), and authority mockery (5 times, 3.87%).